2012
DOI: 10.2147/ijn.s30467
|View full text |Cite
|
Sign up to set email alerts
|

Peptides complementary to the active loop of porin P2 from Haemophilus influenzae modulate its activity

Abstract: Abstract:Haemophilus influenzae type b (Hib) is one of the leading causes of invasive bacterial infection in young children. It is characterized by inflammation that is mainly mediated by cytokines and chemokines. One of the most abundant components of the Hib outer membrane is the P2 porin, which has been shown to induce the release of several inflammatory cytokines. A synthetic peptide corresponding to loop L7 of the porin activates JNK and p38 mitogenactivated protein kinase (MAPK) pathways. We report a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Accumulating evidence has suggested that the regulation of transcriptional factors and the subunit composition by porin stimulation may affect the adaptive immune mechanism to modulate the production of biologically active proteins or peptides. The engagement of multiple pathways during signal transmission makes the possible use of molecular inhibitors as therapeutic agents very difficult; although recent findings show that peptides complementary to loop regions have a certain ability to block the activity of the porin [86]. …”
Section: Porins Induced Signaling Pathwaysmentioning
confidence: 99%
“…Accumulating evidence has suggested that the regulation of transcriptional factors and the subunit composition by porin stimulation may affect the adaptive immune mechanism to modulate the production of biologically active proteins or peptides. The engagement of multiple pathways during signal transmission makes the possible use of molecular inhibitors as therapeutic agents very difficult; although recent findings show that peptides complementary to loop regions have a certain ability to block the activity of the porin [86]. …”
Section: Porins Induced Signaling Pathwaysmentioning
confidence: 99%
“…Measurement of human hs-CRP in serum was performed using the nephelometric technique (Minineph TM, the Binding Site Ltd, PO Box 11712, Birmingham, B14 4ZB, U.K.) (Erlandsen & Randers, 2000). Human IL-6 was measured by AviBion Human ELISA kits (Orgenium Laboratories Business Unit, Vantaa, Finland) according to the manufacturer's recommendations (Cantisani et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory biomarkers, including CRP and IL-6 are increased in various inflammatory conditions and are useful in studying thalassemia and other disease states, including heart disease (Cantisani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of these surface-exposed loops are of considerable interest, and numerous studies have shown their importance in terms of hostpathogen interactions [3]. In particular, extracellular loops have been shown to bind specific cellular receptors, to mediate signalling, and to modulate the immune response [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%